Role of γδ T cells in exacerbated airway inflammation during reinfection of neonatally primed mice in adulthood. Issue 12 (31st August 2017) - Wu, Jianqi; Xu, Lei; Han, Xu; Hu, Haiyan; Qi, Feifei; Bai, Song; Chai, Ruonan; Teng, Yuee; Liu, Beixing
Abstract : Age at primary infection with respiratory syncytial virus (RSV) is a crucial factor in determining the outcome of reinfection. However, how neonatal RSV infection affects the immune system and renders the host more susceptible to reinfection in later life is poorly understood. In the present study, by using BALB/c mice that were first infected with RSV as neonates, the role of γδ T cells in the development of airway inflammation during reinfection in adulthood was investigated. We found that neonatal RSV infection resulted in an aggravated infiltration of mononuclear cells in bronchoalveolar lavage (BAL) fluids, in parallel with a significant increase in the levels of type 2 cytokines in lungs on day 4 after reinfection. Since the numbers of total γδ T cells as well as activated γδ T cells, particularly IL‐4‐, IL‐5‐, and IL‐13‐producing γδ T cells, were enhanced markedly in the lungs of neonatally primed mice, we speculate that γδ T cells might participate in the augmented airway inflammation seen during reinfection. Indeed, depletion of γδ T cells attenuated the severity of lung histopathology during reinfection. Meanwhile, treatment of neonatal mice with anti‐TCRδ mAb diminished not only the numbers of neutrophils, eosinophils, and lymphocytes, but also the levels of IL‐4, IL‐5, and IL‐13 in the lungs after reinfection in adulthood, suggesting that γδ T cells, particularly Th2‐type γδ T cells might play a critical role in exacerbating the pulmonary tissue pathology during reinfection of adult mice that were first infected as neonates.